Reviewing How Preservice Teachers Are Prepared to Teach Reading Processes: What the Literature Suggests and Overlooks. (June 2019) - Hikida, Michiko; Chamberlain, Katharine; Tily, Susan; Daly-Lesch, Anne; Warner, Jayce R.; Schallert, Diane L.
Today's world requires attention to all aspects of initial literacy teacher preparation, including how and what preservice teachers learn about the component processes of reading. To address this imperative, a review was conducted of articles published from 2000 to 2018 identified through the CITE-ITEL database (https://cite.edb.utexas.edu ) that reported findings related to reading processes and initial teacher preparation. After an inductive analytic process, the authors organize findings into five focus areas: (a) definitions and delimitations of reading processes, (b) studies of preservice teachers' beliefs about teaching reading processes, (c) research identifying preservice teachers' knowledge gaps and misconceptions, (d) intervention studies aimed at increasing preservice teachers' knowledge, and (e) studies detailing the application of knowledge about reading processes into contexts of pedagogical practice. The discussion considers the current gaps in how reading processes and literacy are conceptualized and possible areas of inquiry related to preservice teacher education and reading processes.